Highly Dispersed Ru–Co Nanoparticles Interfaced With Nitrogen‐Doped Carbon Polyhedron for High Efficiency Reversible Li–O2 Battery - Tong, Zhen; Lv, Chao; Zhou, Yao; Zhang, Peng‐Fang; Xiang, Cheng‐Cheng; Li, Zhen‐Gang; Wang, Zhen; Liu, Zong‐Kui; Li, Jun‐Tao; Sun, Shi‐Gang (Small (Weinheim an der Bergstrasse, Germany), 2022)
The lithium–oxygen (Li–O2) battery with high energy density of 3860 Wh kg−1 represents one of the most promising new secondary batteries for future electric vehicles and mobile electronic devices. However, slow oxygen reduction/oxygen evolution (ORR/OER) reaction efficiency and unstable cycling performance restrain the practical applications of the Li–O2 battery. Herein, Ru‐modified nitrogen‐doped porous carbon‐encapsulated Co nanoparticles (Ru/Co@CoNx–C) are synthesized through reduction of Ru on metal–organic framework (MOFs) pyrolyzed derivatives strategies. Porous carbon polyhedra provide channels for reactive species and stable structure ensures the cyclic stability of the catalyst; abundant Co–Nx sites and high specific surface area (353 m2 g−1) provide more catalytically active sites and deposition sites for reaction products. Theoretical calculations further verify that Ru/Co@CoNx–C can regulate the growth of Li2O2 to improve reversibility of Li–O2 batteries. Li–O2 batteries with Ru/Co@CoNx–C as cathode catalyst achieve small voltage gaps of 1.08 V, exhibit excellent cycle stability (205 cycles), and deliver high discharge specific capacity (17050 mAh g−1). Furthermore, pouch‐type Li–O2 batteries that maintain stable electrochemical performance output even under conditions of bending deformation and corner cutting are successfully assembled. This study demonstrates Ru/Co@CoNx–C catalyst's great application potential in Li–O2 batteries. A composite catalyst of highly dispersed Ru–Co nanoparticles and nitrogen‐doped carbon polyhedron is prepared as Li–O2 cathode. The stable porous carbon structure, uniformly dispersed, and abundant Co–Nx active sites, and the presence of the ultrafine Ru nanoparticles enables efficient and reversible formation and decomposition of Li2O2 with low overpotential and high discharge specific capacity.